PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN MATERI PERUBAHAN ENERGI DI KELAS 4 SEKOLAH DASAR - Veronika Gelu Idan; Ady Saputra; Agustinus Toding Bua (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2024)
Type of research used is research and development or Research and Development which refers to the ADDIE development model which consists of five research stages, namely Analysis, Design, Development, Implementation, Evaluation. The data collection instruments are validation sheets, learning results tests and student motivation questionnaires. Validation results obtained from material experts are 95%, language experts are 93.3%, media experts are 77.3% and practitioner experts are 100% and the average percentage score validation from the four validators was 91.4%. Validation results from material experts, language experts, media experts and practitioner experts show that interactive learning media is very suitable for use in the learning process. Then the results of the limited trial student motivation questionnaire were 81%, the results of the field trial student motivation questionnaire were 82.03%, and the pre-test limited trial student learning test results were only in 3 categories, namely, low, medium and high categories. The post-test for trial students is limited to only 2 categories, namely, the high and very high categories. The post test results of students in the limited trial were 5 students out of a total of 6 students who had achieved the KKM score. The results of the pre-test field trial student learning tests were only in 5 categories, namely, very high, high, medium, low and very low categories. Post-test field trial students were only in 1 category, namely, the very high category. The post test results of students in the field trial were 28 students out of a total of 28 students who had achieved the KKM score.